THE USE OF PROVERBS IN ENHANCING PAREMIOLOGICAL COMPETENCE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The article examines the role of proverbs in fostering paremiological competence among language learners. Paremiological competence, defined as the ability to understand, interpret, and appropriately use proverbs, is a vital component of linguistic and cultural competence. The study highlights how proverbs encapsulate cultural values, norms, and social wisdom, making them effective tools for intercultural communication and understanding. Through task-based language teaching methods and interactive learning strategies, proverbs can engage students in discussions that deepen their comprehension of idiomatic language. The paper also discusses the significance of proverbs in improving vocabulary, grammar, and context-driven understanding of language, particularly in multilingual and multicultural settings. Examples from English and Uzbek proverbs are provided to illustrate how comparative analysis can aid learners in identifying linguistic and cultural parallels. The research concludes with recommendations for integrating proverbs into language curricula as a means to enhance both linguistic proficiency and cultural awareness.